Pengaruh Sistem Pengendalian Internal Terhadap Pencegahan Kecurangan Dengan Efektivitas Audit Internal Sebagai Variabel Moderasi - Ni Komang Laksmi Ayu, Antari; Amlayasa, Anak Agung Bagus; Astuti , Partiwi Dwi (Journal of Culture Accounting and Auditing, 2025)
This study aims to empirically examine the influence of Internal Control (PI) and Internal Audit (AI) Effectiveness on Fraud Prevention (PK) and the moderating role of Internal Audit Effectiveness in strengthening the relationship between PI and PK. This quantitative research uses a survey method with census techniques (saturated samples), involving 35 leaders of People’s Credit Banks (BPR) operating in Denpasar City as respondents. The data were analyzed using Partial Least Squares – Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The test results show two significant key findings. First, Internal Control has been shown to have a positive, significant effect on Fraud Prevention. Second, although Internal Audit Effectiveness does not have a significant direct influence, it has been shown to positively and significantly moderate the relationship between Internal Control and Fraud Prevention. The conclusion of this study confirms that Internal Control is the primary mechanism for fraud prevention. However, its effectiveness is optimal only when it is supported by strict supervision and evaluation by the competent and independent Internal Audit function. The managerial implications of these findings are the importance of BPR investment in maintaining the quality, competence, and independence of the Internal Audit unit to ensure maximum synergy within the framework of anti-fraud governance